THE EFFECT OF STOCK DENSITY OF GOLDEN-MOUTH TURBAN (Turbo chysostomus, L.) ON THEIR SURVIVAL AND GROWTH UNDER AIR WATER LIFT SYSTEM - M.S. Hamzah (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Golden-mouth turban (Turbo chrysostumus, L.) belongs to the phylum of molluscs that inhabits coral reef ecosystem in group. Golden-mouth turban normally uses algae for their food. Study on survival and growth of the juvenile golden-mouth turban focussing on different density under air water lift sys-tem is still limited. This study was conducted on 7 January – 6 May,  2015, in a laboratory to observe the effect of different density on the survival and growth of golden-mouth turban under air water lift system. Based on the analyses of variance (ANOVA), there was no significant different (P>0.05) on mortality rate for different stock density treatment (5 ind., 10 ind., 15 ind., and 20 ind. each in 10 liter water volume). However, based on growth rate, the density of 5 individuals produced the highest monthly growth rate of 1.88 mm/month of shell height, 1.18 mm/month of mouth opening, and 1.1 gr/month of wet weight with the highest daily mean food absorption of 91.55 %. For all treatment, the correlation of shell height and wet body weight exhibited a similar growth pattrern i.e., allometry minor (b<3). Ketwords: Survival, growth, golden-mouth turban (Turbo chrysostumus), stocking density, air water lift system.